Indonesia's Efforts to Maintain Sovereign Rights in the North Natuna Sea After China's Maneuvers - Nirwana, Nirwana (Universitas Labuhanbatu, 2025)
The increasing tension between Indonesia and China in the South China Sea (SCS), particularly around Indonesia’s Exclusive Economic Zone (EEZ), necessitates an in-depth legal analysis of state responses to foreign violations of sovereign rights. This study aims to identify China’s maneuvers and examine the Indonesian government’s response to these actions in the North Natuna Sea (NNS). This is a normative legal research employing an international legal approach. Data were collected through literature review and analyzed qualitatively using a descriptive-analytical method. The findings indicate that China has conducted systematic and continuous maneuvers in the North Natuna Sea. As a coastal state, Indonesia holds sovereign rights in its EEZ; therefore, in response to any violations by other countries that threaten these rights, the Indonesian government may enforce legal measures and formulate strategic policies to defend and protect the area through diplomacy and maritime defense.Keywords: China Maneuvers; Defense; North Natuna Sea; South China Sea; Sovereign Rights